Constitutive modelling of ratcheting behaviour for nickel-based single crystal superalloy under thermomechanical fatigue loading considering microstructure evolution. (October 2020) - Zhang, Bin; Wang, Rongqiao; Hu, Dianyin; Jiang, Kanghe; Hao, Xinyi; Mao, Jianxing; Jing, Fulei
Highlights: The microstructure evolution of a single crystal superalloy under IP TMF and OP TMF is investigated. Phenomenological models are developed to describe the microstructure evolution. A modified crystal plasticity constitutive model considering microstructure evolution is developed. Ratcheting behaviour during the whole lifetime as well as hysteresis loops and microstructure evolution degree are simulated. Abstract: Based on the metallographic observation, the microstructure evolution of nickel-based single crystal superalloy under thermomechanical fatigue (TMF) loading is investigated, and respective phenomenological models of damage and rafting are developed. Considering that the deformation behaviour of material is closely related to their microstructures, new variables involving rafting evolution are incorporated to modify the hardening rule in order to overcome the inaccurate prediction in stable stage of ratcheting behaviour. Furthermore, by combining the continuum damage mechanics, a modified crystal plasticity constitutive model is proposed, and the ratcheting behaviour during the whole TMF lifetime, as well as hysteresis loops, can be simulated accurately.